Challenges for the German Health Care System – Pharmaceuticals - Dietrich, C. F.; Mäurer, M.; Riemer-Hommel, P. (Endoskopie heute, 2014)
We recently addressed the challenges of the German Health Care System (GHCS) in an era of an aging population and economic problems discussing the funding process, hospital management and ambulatory care, with a focus on cost control mechanisms and quality improvement measures. Pharmaceutical issues have not been mentioned in detail. It is of interest that increases in Social Health Insurance (SHI) expenditures on pharmaceuticals in Germany were above the European average in the last decades. There are three main aspects to consider when it comes to discussing the topic of pharmaceuticals in health care services, the efficacy of the drugs, safety issues and cost containment. The paper summarizes pharmaceutical issues as challenges for the German Health Care System.
Keywords: aging population; pharmacoecnomics; hospital; ambulatory Care; health; information technology